Social Determinants of Health in People Living with Psychiatric Disorders: The Role of Pharmacists (Mary Ann Liebert, 2023)
Introduction: Social determinants of health (SDOH) affect outcomes of people living with psychiatric disorders, including substance use disorders. As experts in medication optimization, pharmacists play a vital role in identifying and addressing medication-related problems associated with SDOH. However, there is a paucity of literature on how pharmacists can be part of the solution. Objective: The purpose of this article is to provide a narrative review and commentary on the intersection between SDOH, medication-related outcomes in people living with psychiatric disorders, and the role of pharmacists in addressing them. Method: The American Association of Psychiatric Pharmacists appointed an expert panel to research the issue, identify barriers, and develop a framework for including pharmacists in addressing medication therapy problems associated with SDOH in people with psychiatric disorders. The panel used Healthy People 2030 as the framework and sought input from public health officials to propose solutions for their commentary. Results: We identified potential connections between SDOH and their impact on medication use in people with psychiatric disorders. We provide examples of how comprehensive medication management can afford opportunities for pharmacists to mitigate medication-related problems associated with SDOH. Conclusion: Public health officials should be aware of the vital role that pharmacists play in addressing medication therapy problems associated with SDOH to improve health outcomes and to incorporate them in health promotion programs.